ADDRESSING ADOLESCENT ANGER: A STUDY OF THE NOMINAL GROUP TECHNIQUE AS AN EFFECTIVE SOLUTION - Mohd Imran Yusoff; Nor Shafrin Ahmad; Nor Hernamawarni Abdul Majid; Siti NorDarma Ab Rahman (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study utilized the Nominal Group Technique (NGT) to identify critical factors influencing adolescent anger management, guided by Albert Bandura’s Social Learning Theory (SCT). The primary objective was to pinpoint core components for designing effective anger management strategies for adolescents. Nine experts-comprising trained counseling teachers and mental health professionals-evaluated key factors across three main categories: behavioral, environmental, and personal factors. The key findings revealed that imitation (77.78%) was the most significant behavioral factor, highlighting the crucial role of observational learning in managing anger. The school environment (74.07%) was identified as a vital environmental factor, indicating the significant influence of educational settings on adolescent anger regulation. Additionally, cognitive skills (74.07%) emerged as a key personal factor, underscoring the importance of strengthening problem-solving and critical thinking skills as part of comprehensive anger management strategies. This study provides valuable insights by identifying key intervention factors through a structured expert-driven approach facilitated by NGT. Future research should explore how traditional factors can be incorporated into these strategies and assess the long-term effectiveness of the interventions developed.